2010
DOI: 10.1287/serv.2.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pricing and Inventory Policies: A Strategic Analysis of Dual Channel Supply Chain Design

Abstract: his paper presents a continuous time optimization model for a dynamic pricing and inventory control problem in a dual-channel supply chain system. We consider a manufacturer's redesign of traditional channel structures, based on customer behaviors, by engaging in direct Internet sales. While the manufacturer and its retailer set optimal pricing and inventory policies dynamically, this study considers both vertical integration and competition of two channels. For the former case, a continuous time optimal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Xia et al (2017) found that consumers' product return behavior and the retailer's service cost and investment affect the manufacturer's incentive to open a direct channel. Moon et al (2010) found the optimal channel strategy of the manufacturer and its retailer is based on consumers' value and surplus. They examined both the competition and vertical integration of the dual channels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xia et al (2017) found that consumers' product return behavior and the retailer's service cost and investment affect the manufacturer's incentive to open a direct channel. Moon et al (2010) found the optimal channel strategy of the manufacturer and its retailer is based on consumers' value and surplus. They examined both the competition and vertical integration of the dual channels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Huang and Swaminathan [17] showed that the multiple channel retailers always set a higher price for the products than do the single channel retailers. Moon et al [26] argued that when the customers prefer the online channel, the channel conflict become fiercer. Hua et al [14] examined the optimal decisions of delivery lead time and prices in a centralized and a decentralized dualchannel supply chain.…”
Section: Multiple Channel Competitionmentioning
confidence: 99%
“…Moon et al [22] addressed a dual-channel supply chain system using an optimization model under continuoustime conditions. Their proposed model covered inventory control and dynamic pricing problems and formed for a producer which seeks to maximize its profit through two channels.…”
Section: Literature Reviewmentioning
confidence: 99%